Penerapan Ketentuan Praktik Sita Jaminan atas Saham Guna Memperoleh Kepastian Hukum - Adelia Audiana Gerchikova; Anita Afriana; Sherly Ayuna Putri (Universitas Medan Area, 2020)
This research is intended to assert the legal basis for Shares Guarantee Seizure implementation, and execution mechanism towards Court Judgement of Permanent Legal Force, based on positive laws as an actual legal basis in order to achieve legal certainty as a practice of Shares Guarantee Seizure. The research is conducted through normative juridical method approach with descriptive analytical research specifications, and data analysis performed with qualitative methods. This study results shown, first, the actual legal basis for the efforts of Shares Guarantee Seizure is contained in article 227 section (1) of HIR in conjunction with Article 511 of The Indonesian Civil Code, as long as its implementation fulfills the basic requirements. Secondly, there are several distinct in the execution mechanisms of Shares Guarantee Seizure towards limited companies and both mechanisms have not been asserted in HIR, therefore the rule itself became unclear, whereas rules supposed to achieve legal certainty. To obtain legal certainty, new product regulations for Procedure of Civil Law are required in legislation (wet) arrangement, which should accommodate most of legal issues dynamics in Indonesia.